Rationale, design, and baseline features of a randomized controlled trial to assess the effects of statin for the secondary prevention of stroke: the Japan Statin Treatment Against Recurrent Stroke (J‐STARS). Issue 2 (9th September 2013) - Nagai, Yoji; Kohriyama, Tatsuo; Origasa, Hideki; Minematsu, Kazuo; Yokota, Chiaki; Uchiyama, Shinichiro; Ibayashi, Setsuro; Terayama, Yasuo; Takagi, Makoto; Kitagawa, Kazuo; Nomura, Eiichi; Hosomi, Naohisa; et al.
<x xml:space="preserve">Abstract</x> Background Although statin therapy is beneficial for preventing first strokes, the benefit for recurrent stroke and its sub‐types remains unknown in Asian populations. The aim of this study is to examine the role of pravastatin in the secondary prevention of stroke in Japanese patients. Methods This is a multicenter, randomized, open‐label, parallel group study of patients with noncardioembolic ischemic stroke (atherothrombotic infarction, lacunar infarction, and infarction of undetermined etiology). All patients were diagnosed with hyperlipidemia and with a total cholesterol level between 180 and 240 mg/dl at enrollment. Patients in the treatment group receive 10 mg/day of pravastatin, and those in the control group receive no statin treatment. The primary end‐point is the recurrence of stroke, including transient ischemic attack. The secondary end‐points include the onset of respective stroke sub‐types and functional outcomes related to stroke. The patients were enrolled for five‐years and will be followed up for five‐years. Results A total of 1578 eligible patients (age: 66·2 years, men: 68·8%), including 64·2% with lacunar infarction, 25·4% with atherothrombotic infarction, and 10·4% with infarction of undetermined etiology were included in this study. Lipid levels were generally well controlled (total cholesterol: 210·0 mg/dl, low density lipoprotein cholesterol: 129·5 mg/dl) at baseline. In addition, the disability of patients was relatively mild, and cognitive function was preserved in the majority of patients. Conclusion This article reports the rationale, design, and baseline features of a randomized controlled trial to assess the effects of statin for the secondary prevention of stroke. Follow‐ups of patients are in progress and will end in 2014.